149k views
1 vote
Which one is the correct answer, thank u

Which one is the correct answer, thank u-example-1
User Tochukwu
by
5.9k points

1 Answer

4 votes

Answer:

C

Explanation:

The rule tells you that (x,y) -> (x + 1, y - 3), so you take each vertice and add one to the x-values, and subract 3 from the y-values.

(-6, 4) -> (-6 + 1, 4 - 3) which simplifies to (-5, 1)

(-3, -2) -> (-3 + 1, -2 - 3) which simplifies to (-2, -5)

(2, 1) -> (2 + 1, 1 - 3) which simplifies to (3, -2)

User Niyas Nazar
by
5.9k points